Teleconsultation for pediatric patients with type 1 diabetes mellitus during the COVID-19 pandemic: experience of a university hospital in Brazil - Yasmin Eugênia Santana; Raphael Del Roio Liberatore, Junior (Elsevier, 2022)
Objective: Evaluate the impact of teleconsultation on glycemic control and prevention of acute complications related to diabetes mellitus in children and adolescents treated in a reference hospital during the COVID-19 pandemic in 2020. Method: Descriptive study of data from pediatric diabetic patients who received teleconsultation between April and September 2020. Results: During this period, 143 diabetic patients were evaluated, with a median of 3.4 teleconsultations per patient in the studied period, requiring adjustment of insulin doses in 84.6% of cases. The hospital admission rate was 8,4% due to diabetic decompensation. The metabolic control (HbA1c) became worse in 46% of the sample and improved in 37%. Conclusion: The teleconsultation promoted health care for patients with diabetes mellitus during the COVID-19 pandemic but was not able to guarantee adequate glycemic control.